Istishna in the Community from Various Traditions, Community Needs as Subjects of Buying and Selling: Vol I No.2 2024 - Fadila, Fadila; Firdaus, Rayyan (JAMBE: Jurnal Akuntansi Manajemen Bisnis dan Ekonomi, 2024)
Based on the daily life of society which occurs very frequently, transactions are always carried out in social life, from various circles, often carrying out transaction activities whose terms are unknown and have been taught since ancient times, even by the Prophet Muhammad SAW. is the Ishtishna transaction. The Istishna transaction approach, which has existed for a long time, was introduced to the Islam, then followed by nonIslam and then taught from a different perspective, of course influences the halalness of buying and selling transactions carried out by the community. Carrying out transactions with a contract in advance with a down payment, in installments, or in full at the end of the goods being made or produced makes Istishna transactions a profitable buying and selling method with a win-win solution for both sellers and buyers. mutual respect with trust in the agreement at the start. transactions carried out. This journal article uses a qualitative ethnographic method approach which aims to provide an overview of past to present societal traditions from various aspects of societal needs as subjects of istishna buying and selling transactions by observing the nature/behavior of society from time to time. time. Which results in various types of transactions from various institutions that use Istishna transactions carried out by the public, both those who are aware that it is a transaction using the Istishna approach and those who are not aware of it.